Serous papillary cystadenofibroma combined with extended external genital endometriosis - E. M. Syrkashev; A. E. Solopova; A. V. Asaturova (Акушерство, гинекология и репродукция)
Ovarian cystadenofibroma (CAF) is a rare ovarian tumor originating both from epithelial and stromal components being, however, classified as epithelial tumors. CAF prevalence among all ovarian tumors does not exceed more than 1.7 %. CAFs are commonly asymptomatic, in extremely rare cases of large tumor or ovarian torsion pain sensation may be noted. External genital endometriosis (EGE) is a chronic gynecological disorder that occurs in women of reproductive age and cause infertility and pelvic pain. EGE prevalence comprises around 10 % in women of reproductive age, 20–50 % in women with infertility, and almost 90 % in women with chronic pelvic pain. Magnetic resonance imaging (MRI) is method of choice in diagnostics of such pathology due to the high natural soft tissue contrast and functional techniques such as diffusion-weighted images (DWI) and dynamic contrast enhancement (DCE). Surgery planning, necessity for systemic therapy or follow-up directly depend on imaging and diagnostic laparoscopy results. Here we present a clinical case of rarely combined serous papillary CAF with extended EGE accompanied with consequences of intra-tumoral hemorrhage. Case study demonstrates main visualization characteristics that provide correct differential diagnosis and exclude malignancy transformation.